2018
DOI: 10.1080/00918369.2017.1422938
|View full text |Cite
|
Sign up to set email alerts
|

Violence as Mediating Variable in Mental Health Disparities Associated to Sexual Orientation Among Mexican Youths

Abstract: In this study, we explored the role of sex as an effect-modifying variable in the association between sexual orientation and mental health in Mexican youth. In addition, we tested if violent experiences in the family and the school and attitudes toward homosexuality could act as mediating variables in such association. Data from three representative surveys performed in 2007, 2009, and 2013 among Mexican high school students were analyzed. Two dimensions of sexual orientation were evaluated: romantic partnersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some of the characteristics of the participants in our study are similar to those of probabilistic samples. For example, Mexican youth who have samegender romantic relationships tend to live in households in which the household head has higher education (Mendoza-Pérez & Ortiz Hernández, 2019). In addition, similar to our sample, most men who have sex with other men (MSM) who are recruited in LGBT avenues have an education level of a bachelor's degree or higher (Bautista-Arredondo et al, 2013).…”
Section: Participantsmentioning
confidence: 64%
“…Some of the characteristics of the participants in our study are similar to those of probabilistic samples. For example, Mexican youth who have samegender romantic relationships tend to live in households in which the household head has higher education (Mendoza-Pérez & Ortiz Hernández, 2019). In addition, similar to our sample, most men who have sex with other men (MSM) who are recruited in LGBT avenues have an education level of a bachelor's degree or higher (Bautista-Arredondo et al, 2013).…”
Section: Participantsmentioning
confidence: 64%
“…Furthermore, numerous studies have reported that sociodemographic (e.g., sexual orientation, sex role, education, income, religion, and race), psychological (e.g., gender role, self-esteem, social support, and violence), and social/cultural variables (discrimination, prejudice, and piety) are closely related to sexual minorities’ health status and life satisfaction (Lazarevic, Holman, Oswald, & Kramer, 2015; Lo, Kim, Small, & Chan, 2019; Mendoza-Perez & Ortiz-Hernandez, 2019; Meyer, 2003; Perales, 2018; Pollitt, Mallory, & Fish, 2018; Powdthavee & Wooden, 2015; Shangani, Gamarel, Ogunbajo, Cai, & Operario, 2019; Starr & Zurbriggen, 2017; Steward, Miege, & Choi, 2013; Wang et al, 2019). In particular, bisexuals are at double the risk of experiencing prejudices from both homosexuals and heterosexuals and have a higher likelihood to develop health problems than homosexuals and heterosexuals do (Balsam & Mohr, 2007).…”
mentioning
confidence: 99%
“…Additionally, factors such as mental health and substance use that have previously been linked to inflammation ( Beurel et al, 2020 ; García-Calvo et al, 2020 ), violence victimization ( Bhavsar and Ventriglio, 2017 ; Porcerelli et al, 2003 ), and LGB identity ( Mendoza-Pérez and Ortiz-Hernández, 2019 ; Fish and Baams, 2018 ), should also be examined to better understand the victimization, and inflammation associations. Interestingly, we find that our proposed model from identity to low-grade inflammation via life-course cumulative victimization was not supported for individuals with LGB and Hispanic identity.…”
Section: Discussionmentioning
confidence: 99%